A NEW NI-RICH STEVENSITE FROM THE OPHIOLITE COMPLEX OF OTHRYS, CENTRAL GREECE - Christidis G.E.; Mitsis I. (My University, 2006)
The first occurrence of Ni-rich stevensite found in the ophiolite complex of Othrys, Central Greece is described. The stevensite, which develops in cracks in a host serpentinite, formed at the expense of serpentine. Two varieties of stevensite have been described: a Mg-rich, Ni-poorer variety with 0.4-1.2 octahedral Ni atoms per half formula unit (p.h.f.u.) and a Ni-rich variety with >2 Ni atoms p.h.f.u. The layer charge in both varieties is -0.24 p.h.f.u.. Stevensite layers are completely separated when dispersed in dilute polyvinylpyrrolidone (PVP) solutions and begin to convert to talc after heating at 250°C for 90 min. Total conversion to talc is observed at 550°C. Formation of Ni-rich stevensite took place at ambient temperature during supergene processes. The scarcity of Ni-rich stevensite occurrences in nature is attributed to the metastability of smectite and to the analytical procedures used in previous studies. Stevensite is considered a phase containing domains with variable numbers of octahedral vacancies. A new experimental protocol is proposed for the determination of Ni-rich stevensite, based on a combination of XRD after solvation with various organic liquids and subsequent heating at 750°C. Copyright © 2006, The Clay Minerals Society.
Keywords: GREECE; METASTABILITY; NI-RICH STEVENSITE; OCTAHEDRAL VACANCY; OTHRYS OPHIOLITE COMPLEX; PVP; SERPENTINE; SUPERGENE ALTERATION; TALC; XRD